Use of a bacterial hygromycin B resistance gene as a dominant selectable marker in Neurospora crassa transformation - C. Staben; B. Jensen; M. Singer; J. Pollock; M. Schechtman; J. Kinsey; E. Selker (Fungal Genetics Reports, 1989)
Dominant transformation markers allow maximum flexibility in the choice of transformation recipients.